Dispatching after Producing: The Supply of Non-Renewable Resources - Julien Daubanes; Pierre Lasserre (Center for Economic Studies and ifo Institute (CESifo), 2014)
There exists no formal treatment of non-renewable resource (NRR) supply, systematically deriving quantity as function of price. We establish instantaneous restricted (fixed reserves) and unrestricted NRR supply functions. The supply of a NRR at any date and location not only depends on the local contemporary price of the resource but also on prices at all other dates and locations. Besides the usual law of supply, which characterizes the own-price effect, cross-price effects have their own law. They can be decomposed into a substitution effect and a stock compensation effect. We show that the substitution effect always dominates: a price increase at some point in space and time causes NRR supply to decrease at all other points. This new but orthodox supply setting extends to NRRs the partial equilibrium analysis of demand and supply policies. The properties of restricted and unrestricted supply functions are characterized for Hotelling (homogenous) as well as Ricardian (non homogenous) reserves, for a single deposit as well as for several deposits that endogenously come into production or cease to be active.
Keywords: Q38; D21; H22; 330; allocating inventories; allocating reserves; supply theory; price effect; substitution effect; stock compensation effect; green paradox; spatial leakage